Association between school racial/ethnic composition during adolescence and adult health. (March 2021) - Dudovitz, R.N.; Biely, C.; Barnert, E.S.; Coker, T.R.; Guerrero, A.D.; Jackson, N.; Schickedanz, A.; Szilagyi, P.G.; Iyer, S.; Chung, P.J.
Abstract: Objectives: School racial/ethnic segregation in U.S. schoolsDifferences in school racial/ethnic composition may increase health disparities by concentrating educational opportunities that confer long-term health benefits in schools serving predominantly wwhite students. For racial minority students, high concentrations of white students may increase exposure to racismis also associated with psychologicstress, which may ultimately reduceing the long-term health benefits from educational opportunities. Meanwhile associations of racial/ethnic academic tacking within schools and health have been mixed. We sought to test whether: 1) differences in racial/ethnic composition between schools and, 2) racial/ethnic distribution of students in academic tracks within schools are associated with long-term health benefits or risks for white, Black and Latinx students. Methods: We analyzed the National Longitudinal Study of Adolescent to Adult Health (12, 438 participants, collected 1994–2008), to test whether the school-level segregation (percent of non-Latinx white students at participants' school during adolescence) was associated with adult health outcomes at ages 18–26 & 24–32, controlling for contextual factorscomparing Black, Latinx, and white students, and controlling for contextualf factors. A secondary analysis explored whether racial/ethnic cohorting across levels of English courses was associated with each health outcome. Results: Attending a school with a higher percent of white students was associated with higher adult depression scores, substance abuse, and worse self-rated health for black Black students; lower depression scores, better self-rated health, and alcohol abuse for white students; and no health differences for Latinx students. Greater within school racial/ethnic cohorting across English courses was associated with increased odds of alcohol abuse for white students; decreased odds of alcohol abuse for Black and Latinx students; and decreased odds of drug abuse for Black students. Conclusion: Among Bblack youth, attending a school with a higher percentage of white students is associated with worse behavioral health in adulthood. Understanding the potential impacts of school racial/ethnic composition on health is critical to designing policies that maximize access to opportunity and health.Education policies should comprehensively address school quality and racism to maximize adult health. Highlights: This study examined school racial/ethnic composition and long-term health. Black students in higher-percentage white schools had worse adult health. White students in higher-percentage white schools had better adult health. Black students in schools with lower racial/ethnic cohorting had worse health. Latinx students in schools with lower racial/ethnic cohorting had worse health.